2017
DOI: 10.1016/j.carbon.2017.01.097
|View full text |Cite
|
Sign up to set email alerts
|

Impact of UV irradiation on multiwall carbon nanotubes in nanocomposites: Formation of entangled surface layer and mechanisms of release resistance

Abstract: Multiwall carbon nanotubes (MWCNTs) are nanofillers used in consumer and structural polymeric products to enhance a variety of properties. Under weathering, the polymer matrix will degrade and the nanofillers may be released from the products potentially impacting ecological or human health. In this study, we investigated the degradation of a 0.72 % (by mass) MWCNT/amine-cured epoxy nanocomposite irradiated with high intensity ultraviolet (UV) light at various doses, the effects of UV exposure on the surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Numerous theoretical and experimental studies have demonstrated this capability for carbon nanotubes (CNTs) and similar results have been reported for graphene (G), too . Therefore, both CNTs and graphene have been added in small amount to polymer matrix in order to convey the radical scavenging functionalities to the composite film. In most of the cases, when polymer composites containing a few CNT percentage (0.2–5 wt%) are exposed to strong UV irradiation, at higher temperature (50–60 °C) in oxygen atmosphere, the presence of the filler delay the photooxidation process.…”
Section: Introductionmentioning
confidence: 66%
“…Numerous theoretical and experimental studies have demonstrated this capability for carbon nanotubes (CNTs) and similar results have been reported for graphene (G), too . Therefore, both CNTs and graphene have been added in small amount to polymer matrix in order to convey the radical scavenging functionalities to the composite film. In most of the cases, when polymer composites containing a few CNT percentage (0.2–5 wt%) are exposed to strong UV irradiation, at higher temperature (50–60 °C) in oxygen atmosphere, the presence of the filler delay the photooxidation process.…”
Section: Introductionmentioning
confidence: 66%
“…The resistance ratio of the composite material (ME) decreases under UV light. Photo-induced depolymerisation and erosion processes results in a lower resistance connection between the CNTs and changes the electrical properties of the composite sample [26,27]. These interactions between the matrix material and the carbon nanotubes are known and is part of new sensor concepts [26,28].…”
Section: Resultsmentioning
confidence: 99%
“…less than 200 h, the rates of carbonyl formation were found very similar to that observed for unfilled polyethylene film but at longer irradiation times the carbonyl formation was found to increase for lower MW-CNTs contents (0.1 wt %, 0.2 wt % and 0.5 wt %), and to decrease for higher MW-CNTs contents (1 wt % and 2 wt %) [ 33 ]. The stabilization effect of MWCNTs was also found for other polymers: epoxy [ 34 , 35 , 36 , 37 ], Thermoplastic Polyurethane (TPU) [ 38 ], Polyamide 6,6 (PA6) [ 39 , 40 , 41 ], PLA [ 42 ] and isotactic polypropylene (iPP) [ 40 , 43 ]. Epoxy containing MWCNTs exposed to UV radiation degraded at a much slower rate than the unfilled epoxy or the epoxy/nanosilica composite [ 37 ].…”
Section: Introductionmentioning
confidence: 95%